Hubungan Kadar Insulin Pankreas dan Kadar Glukosa Darah pada Model Tikus Wistar Jantan setelah Diinduksi Bisphenol-A - Mala Hayati; Zahreni Hamzah; Ari Tri Wanodyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2020)
This study was to determine the relation between pancreas insulin levels and blood glucose levels in male wistar rat models after Bisphenol-A induction. This research was a laboratory experimental study with a randomized separate pretest-post test control group design. The samples consist of 12 rats that divided into 2 groups. Each group consist 6 rats. In the treatment group, bisphenol-a is given peroral at a dose of 20mg/ kg for 28 days. Pancreas insulin levels will be examined by ELISA and blood glucose levels measurement done by glucometer before decapitation procedure. The data were analyzed by Pearson correlation test for blood glucose levels and pancreas insulin levels (p <0.05). The results showed r count (0.802), sig. 2 tailed (0.002), which mean there is a strong correlation and a positive relation between pancreas insulin levels and blood glucose levels. The higher the pancreas insulin levels, the blood glucose levels will also increase. There was a strong correlation and a positive relation between pancreas insulin levels and blood glucose levels, which is when pancreas insulin levels elevated, blood glucose levels will also be increased in BPA-induced rat with dose of 20 mg / kg / day for 28 days.